Tracing pathogens in the food chain - Brul, Stanley; Fratamico, Pina M.; McMeekin, T. A. 1945- (Woodhead Publishing in food science, technology, and nutrition ;, 2011)
Successful methods for the detection and investigation of outbreaks of foodborne disease are essential for ensuring consumer safety. Increased understanding of the transmission of pathogens in food chains will also assist efforts to safeguard public health. Tracing pathogens in the food chain reviews key aspects of the surveillance, analysis and spread of foodborne pathogens at different stages of industrial food production and processing. Part one provides an introduction to foodborne pathogen surveillance, outbreak investigation and control. Part two concentrates on subtyping of foodborne pathogens, with chapters on phenoytypic subtyping and pulsed-field gel electrophoresis, as well as emerging methods. The vital topics of method validation and quality assurance are also covered. The focus in Part three is on particular techniques for the surveillance and study of pathogens, such as protein-based analysis, ribotyping and comparative genomics. Finally, Part four focuses on tracing pathogens in specific food chains, such as red meat and game, dairy, fish and shellfish. With its distinguished editors and international team of contributors, Tracing pathogens in the food chain is a standard reference for researchers, public health experts and food industry professionals concerned with the study and control of foodborne disease. Reviews key aspects of the surveillance, analysis and spread of foodborne pathogensProvides an overview of method validation and quality assuranceExamines the tracing of pathogens in specific food chains, such as red meat, game and dairy.